THE CONCEPT OF MENTAL HEALTH IN ISLAM - Sintong Tampubolon; Afdhal Ilahi (PT. Jurnal Center Indonesia Publisher, 2026)
This journal focuses on mental health. The purpose of this paper is to understand how people with mental health are treated in Islam. To further narrow this discussion, the author discusses the concept of mental health in Islam, the characteristics of people with mental health in the Quran, and the characteristics of people with mental illness in the Quran. This article was compiled using a literature review method obtained from reading various books, journals, and other publications related to mental health.